The Effectiveness of Exhaust Fan Rotation with Microcontroller for Indoor CO2 Gas Concentration Control System - Hartanto, Sri; Priyono, Tri Ongko; ., Triono (International Journal of Applied Sciences and Smart Technologies, 2023)
A dangerous gas that is harmful to human health and is generally found in the room is carbon dioxide (CO2) gas, which is produced from the accumulation of cigarette smoke. In order to overcome the CO2 gas concentration in the room, it is necessary to develop a device that can control the CO2 gas concentration in the room and that processes the CO2 gas detection results from the MQ-2 sensor. In this research, a device simulation was created that can control the CO2 gas concentration produced by accumulated cigarette smoke in a simulation room measuring 15 cm long, 20 cm wide, and 15 cm high with two CO2 gas release ventilation holes, each with a diameter of 3.5 cm, using the exhaust fan rotation and a microcontroller type Arduino UNO as the control unit. The effectiveness of using a microcontroller of the type Arduino UNO to process the CO2 gas detection results from the MQ-2 sensor can be seen in how the exhaust fan works to release CO2 gas from the simulation room. From the results of this research, it can be seen that the effectiveness of the exhaust fan rotation in controlling the CO2 gas concentration detected by the MQ-2 sensor looks good where the CO2 gas concentration can be controlled under 350 ppm.